IDENTIA Registry: Incidence of Deep Vein Thrombosis in Medically Ill Subjects at High Risk in Indonesia: A Prospective Study - Karmel L. Tambunan; Johan Kurnianda; Catharina Suharti; Shinta O. Wardhani; Lugyanti Sukrisman; Noorwati Soetandyo; Ni Made R.A. Rena; Nuzirwan Acang; Andi F. Benyamin; Muhammad Darwin Prenggono; Dairon Gatot; Trinugroho Heri Fadjari; et al. (Acta Medica Indonesiana)
Background: medically ill hospitalized patients are at risk of deep vein thrombosis (DVT) and consequentially have high chances of mortality. In Indonesia, there is disparity in healthcare facility and data on incidence of DVT in this multi-ethnic, geographically unique country with large population are limited. Hence, we determined the incidence of DVT and evaluated mean Wells score among medically ill hospitalized persons at increased risk. Methods: in this multicenter, prospective, observational registry in Indonesia, subjects (age >40 years) with acute medical illness (like cancer, acute infection, or severe respiratory disease) confined to bed for >3 days were enrolled between January 2016 and November 2017. Data for medical history, Wells score, and DVT diagnosis with compression ultrasonography (CUS) were recorded. DVT incidence was analyzed in eligible and evaluable groups. Data were analyzed by descriptive method. Results: out of 360 subjects enrolled, 334 were included in the eligible group for analyses. CUS could not be performed in 26 subjects. Thus, 308 subjects who completed the study were included in the evaluable group. Javanese were predominant in the eligible group and obesity was the most common medical history at presentation. Overall, incidence of DVT in eligible and evaluable patients was 37.1% and 40.3%, respectively. Mean (SD) Wells score and bedridden days were 3 (1.20) and 9 (6.89), respectively. Conclusion: this study indicated that the incidence of DVT is high in medically ill patients in Indonesia and will provide new insights and awareness about DVT in Indonesia.